Large-Scale Education Reform in General Equilibrium: Regression Discontinuity Evidence from India - Comment - David Roodman (Institute for Replication (I4R), 2023)
This paper reanalyzes Khanna (2023), which studies labor market effects of schooling in India through regression discontinuity designs. Absent from the data are four dis-tricts close to the discontinuity; restoring them cuts the reduced-form impacts on schooling and log wages by 57% and 63%. Using regression-specific optimal band-widths and a robust variance estimator clustered at the geographic unit of treatment makes impacts statistically indistinguishable from 0. That finding is robust to varying the identifying threshold and the bandwidth. The estimates of general equilibrium effects and elasticities of substitution are not unbiased and have effectively infinite first and second moments.
Additional information: This paper received a response: Khanna, Gaurav. 2023. Response to "Comment on Khanna (2023)". I4R Discussion Paper Series No. 71. Institute for Replication. https://hdl.handle.net/10419/276970
Keywords: 330